2013
DOI: 10.1186/1479-5876-11-248
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lean and fat mass on bone mineral density and on urinary stone risk factors in healthy women

Abstract: BackgroundThe role of body composition (lean mass and fat mass) on urine chemistries and bone quality is still debated. Our aim was therefore to determine the effect of lean mass and fat mass on urine composition and bone mineral density (BMD) in a cohort of healthy females.Materials and methods78 female volunteers (mean age 46 ± 6 years) were enrolled at the Stone Clinic of Parma University Hospital and subdued to 24-hour urine collection for lithogenic risk profile, DEXA, and 3-day dietary diary. We defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Kim et al ( 12 ) proposed the hypothesis that increased renal inflammation markers may be related to saturated fat intake, podocyte effacement, and elevated proteinuria. Recent studies ( 39 , 40 ) have demonstrated that HFD-treated rats and women with high fat mass index exhibited a spectrum of metabolic abnormalities, the more prominent being dyslipidemia, hyperoxaluria, hypercalciuria, dysproteinuria, low urinary magnesium excretion, loss of bone calcium, and calcium phosphate nephrocalcinosis, results partially shown in the current study. These findings suggest that obesity and fat diet intake may have significantly influence on urine composition in terms of lithogenesis promoters and inhibitors.…”
Section: Discussionsupporting
confidence: 80%
“…Kim et al ( 12 ) proposed the hypothesis that increased renal inflammation markers may be related to saturated fat intake, podocyte effacement, and elevated proteinuria. Recent studies ( 39 , 40 ) have demonstrated that HFD-treated rats and women with high fat mass index exhibited a spectrum of metabolic abnormalities, the more prominent being dyslipidemia, hyperoxaluria, hypercalciuria, dysproteinuria, low urinary magnesium excretion, loss of bone calcium, and calcium phosphate nephrocalcinosis, results partially shown in the current study. These findings suggest that obesity and fat diet intake may have significantly influence on urine composition in terms of lithogenesis promoters and inhibitors.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the data obtained, together with that of Nouvenne et al [16], suggest that the IFM-BMD relationship in women is observed irrespective of their age. Furthermore, comparison of the currentr data with other studies indicate that the body fat-BMD relationship in women, but not in men, is not related to the method of body fat evaluation [18,19].…”
Section: Discussionsupporting
confidence: 62%
“…Inter-and intra-assay coefficients of variation for body fat measurements did not exceed 2%. Fat mass (FM) and lean mass (LM) were further used to calculate ILM and IFM, according to a formula proposed by Nouvenne et al [16]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, we cannot explain this result in our study. Nouvenne et al revealed an increase in urinary phosphorus excretion accompanied by high levels of lean mass 30 . This might explain why the predicted lean mass was negatively related to serum phosphorus in this study.…”
Section: Discussionmentioning
confidence: 98%